A Basic Bibliography for the Study of the Semitic Languages (1973)
contributions by W. H. Ph. Römer, Philo H. J. Houwink ten Cate, L. De Meyer, J. P. Lettinga, K. R. Veenhof, J. H. Hospers, С. H. J. DeGeus, B. Jongeling, T. de Bruin, M. Boertien, H. J. W. Drijvers, A. J. Drewes; “the character of the Bibliography is didactic-selective”.